Numerical demonstration of a topologically-protected electroacoustic transistor - Kuchibhatla, Sai Aditya Raman; Leamy, Michael J. (Frontiers in Acoustics, 2023)
In this paper we conceptualize electroacoustic transistors based on topologically protected interface states in a reconfigurable valley-Hall topological insulator. Using piezoelectric media and active shunt circuits, we numerically model the spatial inversion symmetry breaking in a unit cell to produce topological bandgaps. These gaps are known to host robust modes for wave propagation along an interface. We use two such modes to design a transistor where the wave propagation in one topological channel switches on or off a second topological channel between a source and receiver elsewhere in the structure. Multiple such transistors may be combined to develop logic gates. Further, we develop and simulate the behavior of an electronic circuit which enables the transistor action. Our design opens a pathway to novel wave-based devices which may find applications in structure-based computing, as hybrid multiplexers in communication devices, and as structural switches or embedded sensors in robotics and internet of things.